Correlation between isometric horizontal push force and sprint times in collegiate rugby union players - Dobbs, I. J.; Wong, M. A.; Watkins, C. M.; Barillas, S. R.; Rivera, M.; Coburn, J. W.; Costa, P. B.; Brown, L. E. (Journal of Australian Strength and Conditioning, 2018)
Rugby union requires players to demonstrate horizontal pushing force in activities such as a scrum, ruck, and tackle. Sprinting is also vital for players on offense and defense. Both horizontal pushing force and sprinting require producing maximal force with a forward body lean. Therefore, a relationship between horizontal pushing force and sprint speed may exist for rugby players. Nineteen collegiate rugby players (age= 22.4 ± 2.6 yrs; height= 178.3 ± 6.5cm; mass= 93.9 ± 20.6kg) performed an isometric maximal horizontal push test (MHPT) by pushing into a safety-squat bar with feet hip-width apart and knees bent at 90±, both bilaterally and unilaterally. They performed a 30m sprint with splits at 5m, 10m, 15m, and 30m. Bilateral relative delta force (force- body weight÷body weight)) had a moderate negative correlation with split 1 (r=-0.56), split 2 (r=-0.52), split 3 (r=-0.51), split 4 (r=-0.47), and total time (r=-0.53). Dominant leg relative delta force had a moderate negative correlation with split 1 (r=-0.51), split 2 (r=-0.59), split 3 (r=-0.56), split 4 (r=-0.51), and total time (r=-0.53) while non-dominant leg relative delta force had a moderate negative correlation only with split 1 (r=-0.58). Dominant leg rate of force development (RFD) was significantly greater (915.75 ± 664.77 Nm/s) than the non-dominant leg (632.82 ± 435.40 Nm/s) but the non-dominant leg RFD at 250ms was significantly greater (1867.35 ± 663.78 Nm/s) than the dominant leg (1682.02 ± 619.23 Nm/s). The negative relationships between MHPT and sprinting may be due to similarities of forward lean and plantar flexion. These findings suggest that horizontal force production aids in sprinting. Therefore, rugby athletes should train in the horizontal direction to increase sprint speed.